Stabilization Policies in a Growing Economy: A Comment - Taylor, J. B. (Review of Economic Studies, 1972)
Journal Article Stabilization Policies in a Growing Economy: A Comment Get access John B. Taylor John B. Taylor Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 4, September 1972, Pages 515–519, https://doi.org/10.2307/2296522 Published: 01 September 1972